Exploration of Logistics Market Opportunities: Client Outreach & Integration of Customs Clearance, Freight Forwarding, Warehousing, and Transportation Solutions - Mishra, Rishabh (ATLAS SkillTech University, 2025)
The internship report titled "Exploration of Logistics Market Opportunities and Strategic Positioning: Internship at Sukhin Global Logistics" provides a comprehensive overview of my enriching experience as a Business Development Executive within Sukhin Global Logistics, part of the Shivji Kanji and Company Group. This report encapsulates the valuable insights and practical knowledge gained during this internship program, undertaken as part of my academic and professional development. Throughout the internship, I actively participated in various aspects of logistics management, including client acquisition, market scoping, and promoting integrated logistics solutions. Under the guidance of my reporting manager, Mr. Pradeep Bhanushali, and with training provided by Mr. Kiran Bhadra and Mr. Mahesh Bhanushali, I navigated the dynamic world of logistics, harnessing the opportunity to bridge the gap between theoretical concepts and real-world applications.
Project Report on Exploration of Logistics Market Opportunities: Client Outreach & Integration of Customs Clearance, Freight Forwarding, Warehousing, and Transportation Solutions (2023-2025) Under the Guidance of Prof. Neha Karnik
Keywords: Logistics; Market Opportunities; Strategic Positioning; Business Development; logistics management; theoretical concepts; real-world applications